Fatores críticos do desempenho financeiro de empresas incubadas. - Silva, Tiago Juliano da (2022)
This study aimed to identify the critical factors of financial performance in the incubation period of companies from the perspective of incubated companies. This is available research with a descriptive character. Data collection was carried out by sending the data electronically to 204 incubators, so that they could pass on their incubators, as well as to 214 company representatives through a messaging application on their personal phones. The data were from 202022 month of March and obtained a total of 86 respondents. The study is relevant considering that the knowledge of the critical factors to enable the creation of policies and performance of action by the managers of the incubators with the highest assertiveness indexes. Data analysis was performed using the Structural Equation Model method through SmartPLS 3.0 software, in view of the possibility of relating several variables together. Financial survey results and financial and financial support firms facilitate access to finance provided by finance firms for financial performance. It was not possible to guarantee that the physical infrastructure of the business network and the link in the teaching and research institution promote the performance of companies. This study contributes to the literature by presenting critical performance factors through the perception of incubated companies. The form of practice in incubators can base their work strategies in consideration of what is considered most important for the good performance of their ventures.